2008
DOI: 10.1016/j.jtcvs.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of saphenous vein graft versus right gastroepiploic artery to revascularize the right coronary artery: A prospective randomized clinical, functional, and angiographic midterm evaluation

Abstract: There were no significant patency or major adverse cerebrocardiovascular events rate differences between the 2 groups; however, the number of functional grafts was significantly higher in the saphenous vein graft group. Careful selection of the coronary target is mandatory to obtain good results in gastroepiploic artery grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
3
16
0
1
Order By: Relevance
“…Regarding conduit choice, our results confirmed that SVG was more reliable than arterial grafts when MLD is larger than the cut-off value for arterial grafts and lower than that for SVG. This finding is consistent with the conduit choice for RCA reported by Glineur and colleagues [ 19 ]. If MLD is larger than the cut-off value for SVG, deferral of grafting or stent implantation can be considered.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding conduit choice, our results confirmed that SVG was more reliable than arterial grafts when MLD is larger than the cut-off value for arterial grafts and lower than that for SVG. This finding is consistent with the conduit choice for RCA reported by Glineur and colleagues [ 19 ]. If MLD is larger than the cut-off value for SVG, deferral of grafting or stent implantation can be considered.…”
Section: Discussionsupporting
confidence: 92%
“…Data from our group confirm these early observations [15]. In two prospective randomized trials [10,11 && ], we analyzed the relation between the coronary lesion evaluated by a quantitative method and the functionality of the RGEA vs SVG targeted at the posterior descending artery.…”
Section: Right Gastroepiploic Arterysupporting
confidence: 64%
“…FFR reliably identifies stenoses associated with inducible ischemia with more than 90% accuracy, a rate higher than any other noninvasive test [13][14][15][16]. Several studies have compared these three methods, demonstrating that visual assessment and QCA are of limited value for accurately predicting the significance of most intermediate narrowing and, therefore, predicting the competition phenomenon.…”
Section: Methods Of Coronary Stenosis Evaluation To Predict Flow Compmentioning
confidence: 99%
“…Second, patency of the arterial graft to the moderately stenotic target was not favorable, 8 especially for the in situ gastroepiploic artery. 9 Saphenous vein grafts from the ascending aorta are advantageous, in terms of capacity of high intraluminal pressure and absence of critical complications associated with harvesting the graft. Jeong et al 10 have described that moderate stenosis was predictive of graft failure in arterial grafts, but not in SVG.…”
Section: Discussionmentioning
confidence: 99%